On the uncertainty beneath the name Oithona similis Claus, 1866 (Copepoda, Cyclopoida) - Cepeda, Georgina Daniela (2016)
Te marine cyclopoid Oithona similis sensu lato Claus, 1866, is considered to be one of the most abundant and ubiquitous copepods in the world. However, its minimal original diagnosis and the unclear connection with its (subjective) senior synonym Oithona helgolandica Claus, 1863, may have caused frequent misidentification of the species. Consequently, it seems possible that several closely related but distinct forms are being named O. similis or O. helgolandica without explicit and accurate discrimination. Here the current situation concerning the correct assignment of the two species is revised, the morphological characters commonly used to identify and distinguish each species are summarized, and the nomenclatural implications of indiscriminately using these names in current taxonomic and ecological practice is considered. It is not intended to upset a long-accepted name in its accustomed meaning but certainly the opposite. “In pursuit of the maximum stability compatible with taxonomic freedom” (International Commission of Zoological Nomenclature), we consider that reassessment of the diagnostic characters of O. similis sensu stricto cannot be postponed much longer. While a consensus on taxonomy and nomenclatural matters can be attained, we strongly recommend specifically reporting the authority upon which the identification of either O. similis s.l. or O. helgolandica s.l. has been accomplished.